Satisfaction with outdoor recreation: analyzing multiple data sets - Roemer, Jennifer M., author; Vaske, Jerry, advisor; Donnelly, Maureen, committee member; Morgan, George, committee member (Colorado State University. Libraries, 2012)
Satisfaction has been a focal point in the study of recreation behavior since the 1970s. This thesis contains two articles, both of which use a comparative analysis approach to assess satisfaction ratings of outdoor recreationists. The first article updates a previous comparative analysis article (Vaske, Donnelly, Heberlein, & Shelby, 1982) by analyzing differences in satisfaction ratings reported by consumptive and nonconsumptive recreationists over a 30-year period. Based on the previous analysis, two hypotheses were advanced: (a) consumptive recreationists will report significantly lower satisfaction ratings than nonconsumptive recreationists, and (b) this pattern will remain constant over study years. Data were obtained from published and unpublished sources. A total of 57 consumptive (e.g., hunters) and 45 nonconsumptive (e.g., kayakers) recreation contexts were examined. Each study used the same satisfaction question (i.e., "Overall, how would you rate your day/trip/experience?"). Following Vaske et al. (1982), responses were collapsed into three categories (i.e., "poor/fair," "good/very good," "excellent/perfect"). The independent variables were activity type and study year. Similar to the previous comparative analysis, consumptive recreationists reported lower satisfaction ratings than did nonconsumptive recreationists (hypothesis 1). Consistent with hypothesis 2, the satisfaction ratings remained statistically equivalent for the "poor/fair" and "excellent/perfect" responses among the three categories of study years. Implications for theory, management, and future research are discussed. The second article uses a comparative analysis approach to analyze National Park Service (NPS) visitor satisfaction data over a period of 17 years. Based on theory and prior research, six research questions were proposed. The first set of research questions examined the relationships between visitor satisfaction and study year, park designation, and park region. The remaining research questions concerned the relationships between consensus among visitor satisfaction scores and study year, park designation, and park region. Data were obtained from the online NPS Visitor Services Project (VSP) database (177 projects, n = 81,899). Each project contained the same core satisfaction question (i.e., "Overall, how would you rate the quality of the visitor services provided to you and your group?"), which served as the dependent variable. Independent variables included study year, park designation, and park region. For the first three research questions, three 1-way ANOVAs and one 3-way ANOVA indicated that visitor satisfaction varied by study year, park designation, and park region. Using the Potential for Conflict Index (PCI2), results also addressed the second three research questions by showing that the amount of consensus among visitor satisfaction scores varied by study year, park designation, and park region. Methodological and managerial implications, as well as opportunities for future research, are discussed.
Keywords: comparative analysis; consumptive; National Park Service; nonconsumptive; satisfaction; visitor services project